ANALISIS KINERJA APARAT KELURAHAN DALAM PENYELENGGARAAN PEMERINTAHAN DI KELURAHAN BENGKONG LAUT KECAMATAN BENGKONG KOTA BATAM - Indrawati, Indrawati; Lestari, Linayati (JURNAL TRIAS POLITIKA, 2019)
Urban village headman is the work area as the district under district that is under and is responsible to camat. Kelurahan has the duty and function exercise powers delegated by the Head of government and other governments carry out tasks in accordance with applicable laws. The working relationship with administrative districts hierarchical. Establishment of village is aimed to improve the ability of governance villages fruitfully, effecfive and service to the public in accordance with the level of development and progress of the construction. The purpose of this study was to determine the extent to which the performance of government officials in the Village of Sea Bengkong Bengkong District of Batam. While the benefits of this research in the form of the thesis is expected to be used to qualify for a Bachelor's degree in Public Administration at the Faculty of Social and Political Science Public Administration Program, University of Riau Islands. In this study, the authors used qualitative descriptive method to see how the performance of government officials to the village of governance in Sub Sea Bengkong Bengkong District of Batam. The research was conducted in the village Bengkong Bengkong districts northwest of Batam, data collection techniques used in this study is a Participant Observation (Participant Observatioan) through interviewsand respondence through kuesioner. The results obtained in this study is five indicators or variables that I use in this study, namely productivity of labor, Responsibility, Discipline, Capability Human Resources, and Motivation, which is very influential in the performance of government officials Village on governance in Sub Bengkong Sea Subdistrict Bengkong Batam City is variable ability of human resources, due to the ability of human resources has been owned by the sea Bengkong village officials, the administration of the wheels of government in the village Bengkong sea can run well.